2021
DOI: 10.1371/journal.pone.0248801
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and demographic features of congenital cytomegalovirus infection in an urban area of East Asia: A population-based study

Abstract: Congenital cytomegalovirus (cCMV) infection is the leading environmental cause of childhood hearing impairment. However, its significance remains largely undocumented in many regions of the world. The purpose of this study was to investigate the prevalence and clinical features of cCMV infection in East Asia. Neonates born at a municipal hospital in Taipei were prospectively recruited and underwent concurrent hearing and CMV screenings. Those who failed the hearing screening or screened positive for CMV were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…These include prospective ( n = 20), 18 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 30 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 retrospective ( n = 7) 22 , 23 , 29 , 31 , 35 , 43 , 44 and cross‐sectional studies ( n = 1), 19 conducted in 18 different countries; by region, 16 studies were conducted in Europe, 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 30 , 32 , 34 , 36 , 43 , 44 , 45 five in East Asia, 27 , 29 , 37 , 38 , 39 four in North America 31 , 40 , 41 ...…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These include prospective ( n = 20), 18 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 30 , 32 , 33 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 retrospective ( n = 7) 22 , 23 , 29 , 31 , 35 , 43 , 44 and cross‐sectional studies ( n = 1), 19 conducted in 18 different countries; by region, 16 studies were conducted in Europe, 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 28 , 30 , 32 , 34 , 36 , 43 , 44 , 45 five in East Asia, 27 , 29 , 37 , 38 , 39 four in North America 31 , 40 , 41 ...…”
Section: Resultsmentioning
confidence: 99%
“…The age at last follow‐up ranged between 1 month and 18 years, with 6/28 studies (from three cohorts) including populations with at least 5 years of follow‐up 40 , 41 , 42 , 43 , 44 , 45 (duration unclear for one study). 19 cCMV was identified among children in the included studies via population screening ( n = 13), 18 , 21 , 27 , 29 , 33 , 34 , 38 , 39 , 41 , 42 , 43 , 44 , 45 diagnostic testing of populations with suspected infection or clinical indications ( n = 4), 19 , 20 , 22 , 26 testing of infants born to women with primary CMV infection during pregnancy ( n = 5) 23 , 24 , 32 , 35 , 37 or a combination of these ( n = 6). 25 , 28 , 30 , 31 , 36 , 40 Four studies only included infants born to women with primary maternal CMV infection, 23 , 24 , 32 , 35 whereas eight studies reported the proportion of children born to women with primary and non‐primary maternal CMV infections during pregnancy, 21 , 26 , 28 , 30 , 31 , 33 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations